2002
DOI: 10.1039/b201728h
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected change of the sense of the enantioselective hydrogenation of ethyl pyruvate catalyzed by a Pt–alumina-cinchona alkaloid system

Abstract: In the enantioselective hydrogenation of ethyl pyruvate (EtPy) over beta-isocinchonine (beta-ICN) modified Pt-alumina catalysts, the major enantiomer was (R)-ethyl lactate ((R)-EtLt (ee 50%)) in toluene, while in AcOH (S)-EtLt (ee 60%) was formed; the (R) configuration is opposite to what is expected from the absolute configuration of the cinchonine backbone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 13 publications
(22 reference statements)
2
47
0
1
Order By: Relevance
“…Since no inversion occurred in the hydrogenation of TFAP using AcOH, which would suggest a change in reaction mechanism, we interpreted the unexpected inversion on the basis of postulating a nucleophilic IC [54][55][56][57]62], also proposed by other authors [63][64][65][66]. The proposed nucleophilic IC is supported by earlier studies: (1) under the conditions of the Orito reaction NMR investigations support multipoint interaction between the substrate and chiral modifier; (2) the nucleophilic IC is identifiable in liquid phase by NMR and can also be quantified; (3) IC concentration decreases with increasing acid concentration; (4) there is a correlation between the concentration of this complex and the enantioselectivity of the hydrogenation [67][68][69].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Since no inversion occurred in the hydrogenation of TFAP using AcOH, which would suggest a change in reaction mechanism, we interpreted the unexpected inversion on the basis of postulating a nucleophilic IC [54][55][56][57]62], also proposed by other authors [63][64][65][66]. The proposed nucleophilic IC is supported by earlier studies: (1) under the conditions of the Orito reaction NMR investigations support multipoint interaction between the substrate and chiral modifier; (2) the nucleophilic IC is identifiable in liquid phase by NMR and can also be quantified; (3) IC concentration decreases with increasing acid concentration; (4) there is a correlation between the concentration of this complex and the enantioselectivity of the hydrogenation [67][68][69].…”
Section: Discussionmentioning
confidence: 96%
“…According to the well-known empirical rule, the presence of (8S,9R) cinchonas (CD, QN) promote the formation of (R)-hydroxy compounds in excess, whereas the use of (8R,9S) cinchonas (CN, QD) lead to the excess of (S)-hydroxy compounds in the Orito reaction [8][9][10][11]. In the course of further studies, however, it was found that some derivatives of the parent cinchonas do not follow this rule [54][55][56][57][58][59][60][61]. Inversions of this type are usually designated ''unexpected inversions'' in the literature [62].…”
Section: Discussionmentioning
confidence: 96%
“…It has to be emphasized that in studies using rigid derivatives of cinchona alkaloids only the induction of enantioselectivity has been discussed in details, while issues related to the rate acceleration phenomena were almost entirely omitted [24][25][26][27][28]. In addition, due to the use of unpurified isocinchonines [26] there is certain controversy in results published so far.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, it has been shown that rigid derivatives of cinchona alkaloids, such as a-isocinchonine (a-ICN) and b-isocinchonine (b-ICN) with exclusive open conformation can also induce ED in the hydrogenation of a-keto esters [24][25][26][27][28][29], although the ee values obtained in aprotic solvents were relatively low (ee < 30-40%). The structure of cinchona alkaloids discussed (CD, CN, a-ICN and b-ICN) is given in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The quinolone moiety of the modifier is responsible for the absorption on the Pt surface (Ferri & Bürgi, 2001). An inversion of the enantioselectivity occurs in the asymmetric hydrogenation of the activated ketones by changing the solvent composition, including water and acid additives (von Arx et al, 2001b;Bartók et al, 2002). Hydrogenation of the ethyl pyruvate over Pt/Al2O3 (Huck et al, 2003a) and 4-methoxy-6-methyl-2-pyrone over Pd/TiO2 (Huck et al, 2003b), an equimolar mixture of cinchona alkaloids CD and QD resulted in ee's similar to those obtained with CD alone, while QD gave a high ee of the opposite enantiomers.…”
Section: "Self-supported" and Solid-supported Heterogeneous Catalystsmentioning
confidence: 99%